Functional structure and antimicrobial activity of persulcatusin, an antimicrobial peptide from the hard tick Ixodes persulcatus. Issue 1 (December 2016) - Miyoshi, Naruhide; Saito, Takeshi; Ohmura, Tadahiro; Kuroda, Kengo; Suita, Kazumasa; Ihara, Kohei; Isogai, Emiko
Abstract Background Antimicrobial peptides (AMPs) are considered promising candidates for the development of novel anti-infective agents. In arthropods such as ticks, AMPs form the first line of defense against pathogens in the innate immune response. Persulcatusin (IP) was found in theIxodes persulcatus midgut, and its amino acid sequence was reported. However, the complete structure of IP has not been identified. We evaluated the relation between structural features and antimicrobial activity of IP, and its potential as a new anti-methicillin-resistantStaphylococcus aureus (MRSA) agent. Methods The structure of IP was predicted using homology modeling and molecular dynamics. IP and other tick AMPs were synthesized using a solid-phase method and purified by high-performance liquid chromatography. Methicillin-susceptibleS. aureus (MSSA) and MRSA were used for the minimum inhibitory concentration (MIC) test and short-time killing assay of IP and other tick peptides. The influence of IP on mammalian fibroblasts and colon epithelial cells and each cell DNA and its hemolytic activity towards human erythrocytes were also examined. Results In the predicted IP structure, the structure with an S-S bond was more stable than that without an S-S bond. The MIC after 24 h of incubation with IP was 0.156–1.25 μg/mL for MSSA and 0.625–2.5 μg/mL for MRSA. Compared with the mammalian antimicrobial peptide and other tick peptides, IP was highly effective against MRSA. Moreover, IP showed a dose-dependent bactericidal effect on both MSSA and MRSA after 1 h of incubation. IP had no observable effect on mammalian cell growth or morphology, on each cell DNA and on human erythrocytes. Conclusions We predicted the three-dimensional structure of IP and found that the structural integrity was maintained by three S-S bonds, which were energetically important for the stability and for forming α helix and β sheet. IP has cationic and amphipathic properties, which might be related to its antimicrobial activity. Furthermore, the antimicrobial activity of IP against MRSA was stronger than that of other antimicrobial peptides without apparent damage to mammalian and human cells, demonstrating its possible application as a new anti-MRSA medicine.